IPTEKS BAGI MASYARAKAT PEDESAAN DI DESA TENGKUDAK PENEBEL TABANAN - Darma Oka. I M; I M. Budiasa; M. Suardani (Buletin Udayana Mengabdi, 2011)
Tengkudak Village is one of villages of Tabanan Regency which has tourism potential to attract tourist visits. Tengkudak Village has cool weather because it is located in 700 meter above the sea level with average temperature of 25o C. Beautiful rice terraces with green color during the growing season and yellowish color during the harvesting season. Some part of its area consists of hills with beautiful cliff topography. It is about 92% of the land is used as agriculture and 76% of those are the rice fields with terraces along the hill side. Most of People work as farmers approximately 82.48% which are organized in a traditional agricultural institution called Subak. Education level of the local people is considered still low those are 68.57% elementary school graduated, 3.08% primary school graduated, 11.12% academy school graduated, 1.47% undergraduate (Village monograph, 2008), that’s why the agricultural products cannot be autonomously and professionally processed. In order to anticipate such problem, the Bali State Polytechnic Community Service Team carried out a guided training to the local people especially those who are members of the PKK groups (40 persons). Based on the planned program, the training of the commodities processed to be various kinds of food are: Mangkok Ketela Rambat, Donat Variasi, Donat Ketela Ungu, Kaliadrem, Fried Sesame Ball, Soes Keju Goreng, Muffin Blueberry, Bolu Trio, Pudding Coklat, Pilus Ketela Ungu and so on. The training program for people or Ipteks bagi Masyarakat (IbM) carried out in Tengkudak Village has successfully increased their understanding about tourism in general and has been able to increase their life skills in processing local commodities to be high valued products, at the end, their opportunities of contribution in tourism activity development are getting higher. The items produced by training participants of IbM has met the criteria of product requirement in terms of taste, form, texture, and set-up.